PENINGKATAN PERLINDUNGAN DATA PRIBADI DALAM TRANSAKSI ELEKTRONIK PADA SISWA SEKOLAH MENENGAH PERTAMA DI KOTA MATARAM - Rizki, Novia; Priyambodo, Victoria Kusumaningtyas; Sukma, Paradisa; Almagfira, Anisa Sava (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The Internet is a basic need for all groups in various aspects of life from an educational, social, and economic perspective. Teenagers, as internet users, are at risk of experiencing personal data leakage due to a lack of vigilance. This service activity aims to increase the awareness of junior high school students as millennial teenagers regarding protecting personal data in social media and electronic transactions. It is hoped that with this education, the level of misuse of personal data in Indonesia will decrease. The method used is the lecture method. Activities are carried out through three stages: planning, implementation, evaluation, and reporting. The activity went well, and as a result of the evaluation, participants could sort out data that could be shared and should not be shared with other people, both from the Internet and directly. They knew how to protect personal data.